Burkitt Lymphoma Presented as Acute Lower Back Pain and Revealed by 18F-NaF PET/CT. (May 2016) - Zheng, Wenlu; Chen, Yue; Huang, Zhanwen; Cai, Liang
Abstract : Abstract: A 15-year-old man with acute lower back pain for 7 days underwent 18 F-NaF PET/CT to determine the cause of his symptoms. The PET images revealed irregularly increased 18 F activity in the L1 vertebral body without definite sclerotic changes on CT. However, the corresponding CT images revealed an adjacent paravertebral mass extending into the vertebral foramen without elevated activity on PET. A diagnosis of Burkitt lymphoma was made after pathological examination.